Error Analisis di Penulisan Teks deskriptif - Ragil Pangestu (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
Abstract: The objectives of this research were to figure out and describe the types of grammatical simple present tense errors are found in the one of vocational high school in West Kalimantan 2022/2023. This research used qualitative case study research to analysis the students’ writing ability in descriptive text using present tense based on the four level type of errors: omission, addition, selection and ordering for the one of vocational high school in West Kalimantan. It was conducted on February 2023. The researcher took 12 students as the sample. The subjects of this research was the the one of vocational high school in West Kalimantan 2022/2023 academic year. To collect the data, the researcher used essay writing test with students. After collected the dataafrom the subjects the researcher analysis the dataaby using error analysis method to analyzed qualitative data. The resultaof thisaresearch showedathat the students level of writing skills in descriptive text using present tense is average. The result of this research showed that the students most errors was in error of selection, The most difficult category in writing was in grammatical problem therefore the students should foccus and pay attention on terms of identify reference without ignoring the other aspect of rules of language. Keyword: Error analysis, writing, descriptive text